First-principles WC-GGA and mBJ calculations for structural, electronic, optical and elastic properties of MxGa1-xSb (M=Al, In, B) ternary alloys. (15th November 2022) - Sharma, Nishant; Chandra, Devesh; Rathi, Amit; Singh, A.K.
Abstract: GaSb based ternary alloys have indicated wide range variations in physical, electronic and optical properties. In the present study the structural, electronic, optical and elastic properties of Mx Ga1-x Sb (M = Al, In, B) ternary alloys have been reported and discoursed based on the first-principles investigation. The current work attempts to provide an insight into the evolution of electronic, optical and elastic properties of ternary alloys of Mx Ga1-x Sb (M = Al, In, B) with variation in their constituent compounds. Density functional theory (DFT) operation based on the augmented plane wave + local orbitals (APW + lo) method has been employed to estimate the structure, density of states (DOS), bandstructure, optical and the elastic properties of ternary alloys Mx Ga1-x Sb (M = Al, In, B) for (x = 0, 0.25, 0.50, 0.75, 1) compositions. Computations were performed using the exchange-correlation energy functional from Wu-Cohen, a generalized-gradient approximation (WC-GGA) as well as the original modified Becke-Johnson exchange potential (mBJ) available with the WIEN2k code. As WC-GGA has been observed to underestimate the bandgap, the bandstructure of ternary alloys Mx Ga1-x Sb (M = Al, In, B) for (x = 0, 0.25, 0.50, 0.75, 1) compositions has been reported using modified Becke-Johnson exchange potential (mBJ) method. In case of Alx Ga1-x Sb and Bx Ga1-x Sb alloys, the bandgap values have been observed to deviate strongly from the Vegards law indicating the existence of a bowing parameter while the bandgap values of Inx Ga1-x Sb alloys are in excellent agreement with the reported values and deviate marginally from the Vegards law. Further the optical properties, real and imaginary parts of ϵ(ω) and loss function of Mx Ga1-x Sb (M = Al, In, B) for ternary alloys have been calculated using WC-GGA. The critical points, peaks and shoulders of imaginary part of dielectric function in these alloys have been reported. The elastic properties of these alloys, Bulk modulus (B), Shear modulus (G), Young modulus (E) and Poisson's coefficient (ν) have also been calculated using the Cubic-elastic and Tetra-elastic packages. Graphical abstract: Image 1 Highlights: Accurate parameters for designing optoelectronic devices based on III-Sb ternary alloys. Key properties of technologically important Mx Ga1-x Sb alloys using the augmented plane wave + local orbitals (APW + lo) based formalism. Computations from Wu-Cohen and the original WC-mBJ in excellent agreement with other previously reported theoretical and experimental works. For Alx Ga1-x Sb and Bx Ga1-x Sb WC-mBJ bandgaps deviate indicating a bowing parameter, Inx Ga1-x Sb'bandgaps are in agreement with reported values.